The dominant angle of the Great Pyramid at Giza an alternative theory on how the angle was derived at, from conceptualization up to the actual construction - Sy, Wilson A. (College of Architecture, University of the Philippines Diliman, 2008)
This paper presents an alternative theory on how the dominant angle of the Great Pyramid at Giza was conceptualized and how it was carried out in the actual Construction Process. This paper will also describe how the ancient Egyptians constructed this magnificent structures using local material, their available mathematical knowledge and methods of construction available at the time of its construction. Many scholars in the past have presented various theories on how the dominant angle has been conceptualized. Thirteen (13) theories were presented in the book "The Shape of the Great Pyramid" by Roger Herz-Fischler, and two (2) other theories were presented in the other publications written by Mario Salvadori and Corinna Rossi, regarding the dominant angle of the Great Pyramid. All of these previous theories will be discussed in detail and the applicability of each theory will be discussed for each and every theory. Part of the study will deal with the social and cultural lives of the ancient builders, the construction tools, surveying tools, and the level of mathematical knowledge available to them at the time of the construction of the Great Pyramid at Giza. This paper offers an alternative theory from the viewpoint of structural engineering and practical construction. A theory based on how the form was conceptualized is also offered. Simple mathematics is used in order to compare the dimension of this theoretically constructed pyramid as against the exact dimension of the existing pyramid, measured using modern surveying instruments and documented as as-built drawings, in books and journals.